Estudo do papel das proteínas MSH2 e MSH6 na resposta a danos no DNA em Trypanosoma cruzi - Viviane Grazielle da Silva (2011)
Trypanosoma cruzi, etiologic agent of Chagas disease, presents a highly heterogeneous population structure, characterized by the occurrence of different strains with different biochemical and morphological characteristics. This complex population structure may be correlated with different clinical manifestations of disease, parasite's ability to infect different hostages and geographical distribution presented by the strains. Intra-specific variability can be a result of a balance between genomic stability and generation of genetic variability. Several mechanisms can be involved in maintaining this balance, for example, DNA mismatch repair – MMR. Initial studies on the MMR in T. cruzi led to the discovery that MSH2 - the main protein of the MMR - exists in three isoforms in the parasite, named TcMSH2 A, B and C, according to Tcmsh2 data sequences present in the genome of different strains. Experimental evidence indicates that strains presenting the isoform TcMSH2 A have a more efficient MMR when compared to strains that have TcMSH2 B and/or C isoforms. These observations led us to speculate that differences in MMR activity could account for a lower genetic variability found in strains belonging to MSH2-A haplogroup. In order to investigate the role of the MSH2 protein, we tried to obtain knockout parasites for this gene. Single knockouts parasites are more susceptible to hydrogen peroxide treatment and accumulate more 8-oxoguanine in mitochondrial DNA than wild type parasites, despite the fact that there are no differences after treatment with mutagenic agents. With the aim to better investigate the role of MSH2 in response to oxidative stress, in the present work we investigated MSH2 cellular localization. Antibodies raised against a recombinant form of MSH2 produced in mice were used in immunolocalization and western blot assays. Those experiments have shown that the serum produced in mice is able to recognize the native protein in two different molecular weight proteins, with different subcellular localization. Based on that, we have speculated that the lower molecular weight protein, which is localized at extract fraction correspondent to the cytoplasm, could be involved in mitochondrial DNA repair. Simultaneously, to investigate if TcMSH2 role in response to oxidative damage is dependent of other MMR proteins, we began to characterize them. Two different strategies were used to knockout Tcmsh6. And we also tried to elucidate TcMSH6 subcellular localization after its over-expression in fusion with RFP.